Project Account Regulations In Property Development Preproject Selling System In Indonesia - Satriyo Cahyo Bagaskoro; Yenny Eta Widyanti; Djumikasih (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study aims to analyze the weaknesses in legal regulations related to the use of escrow accounts in the pre-project selling system in Indonesia and to formulate an ideal regulatory model based on a comparative approach. The practice of pre-project selling, which has developed through Sales and Purchase Agreements (PPJB), demonstrates an imbalance in the position of consumers and developers, particularly in terms of fund management. The absence of mandatory escrow account use raises the risk of misuse of funds, default, and potential systemic consumer losses. This study uses normative legal research methods with statutory, conceptual, and comparative approaches, comparing the Indonesian legal system with those of Singapore and Saudi Arabia. The results show that Indonesia still relies on a contractual approach (contract-based protection), which is unable to provide optimal legal protection, especially in the preventive aspect. In contrast, Singapore and Saudi Arabia have adopted a regulatory-based protection approach through mandatory escrow account use, fund segregation, progress-based disbursement, and independent oversight. This difference indicates a normative gap that has impacted weak legal certainty and consumer protection in Indonesia. The conclusion of this study emphasizes the need for legal reconstruction through imperative escrow account regulations, accompanied by an integrated oversight mechanism and effective sanctions. This reform is expected to create preventative legal protection, increase transparency and accountability, and strengthen public trust in the property sector.